Practical Dojo Projects - Zammetti, Frank (Springer, 2017)
The era of professional JavaScript development has arrived! Gone are the days when writing all the client–side code for your applications by hand yourself was the norm. Gone are the days when scrounging around the Internet to find a snippet of code to do something you need could lead to either decent code or utter garbage that you'd surely regret using later. No, writing high–quality JavaScript these days is a whole lot easier with the advent of top–notch libraries that save you time and effort, and one that stands out from most others is Dojo. Dojo is a library like few others: written by some of the best JavaScript coders around today, providing nearly everything you'll need to write modern rich Internet applications, all in one place. From Ajax to widgets, to client–side persistence and language extensions, and many points in between, Dojo has it all.